Rolling-translated EGFR variants sustain EGFR signaling and promote glioblastoma tumorigenicity. Issue 5 (16th December 2020) - Liu, Yi; Li, Zhongjun; Zhang, Maolei; Zhou, Huangkai; Wu, Xujia; Zhong, Jian; Xiao, Feizhe; Huang, Nunu; Yang, Xuesong; Zeng, Rong; Yang, Lixuan; Xia, Zhibo; et al.
Abstract: Background: Aberrant epidermal growth factor receptor (EGFR) activation is observed in over 50% of cases of adult glioblastoma (GBM). Nevertheless, EGFR antibodies are ineffective in clinical GBM treatment, suggesting the existence of redundant EGFR activation mechanisms. Whether circular RNA (circRNA) encodes a protein involved in EGFR-driven GBM remains unclear. We reported an unexpected mechanism in which circular EGFR RNA (circ-EGFR) encodes a novel EGFR variant to sustained EGFR activation. Method: We used RNA-seq, Northern blot, and Sanger sequencing to confirm the existence of circ-EGFR. Antibodies and a liquid chromatograph tandem mass spectrometer were used to identify circ-EGFR protein products. Lentivirus-transfected stable cell lines were used to assess the biological functions of the novel protein in vitro and in viv o. Clinical implications of circ-EGFR were assessed using 97 pathologically diagnosed GBM patient samples. Results: The infinite open reading frame (iORF) in circ-EGFR translated repeating amino acid sequences via rolling translation and programmed −1 ribosomal frameshifting (-1PRF) induced out-of-frame stop codon (OSC), forming a polymetric novel protein-complex, which we termed rolling-translated EGFR (rtEGFR). rtEGFR directly interacted with EGFR, maintained EGFR membrane localization and attenuated EGFR endocytosis and degradation. Importantly, circ-EGFR levels correlated with the EGFR signature and predicted the poor prognosis of GBM patients. Deprivation of rtEGFR in brain tumor-initiating cells (BTICs) attenuated tumorigenicity and enhanced the anti-GBM effect. Conclusion: Our findings identified the endogenous rolling-translated protein and provided strong clinical evidence that targeting rtEGFR could improve the efficiency of EGFR-targeting therapies in GBM.